Quinine Use and the Risk of Exacerbations of Chronic Obstructive Pulmonary Disease: A Nationwide Retrospective Registry Study - Vilstrup F; Sivapalan P; Eklöf J; Jordan A; Biering-Sørensen T; Sperling S; Jensen JUS (International Journal of COPD, 2025)
Frida Vilstrup,1 Pradeesh Sivapalan,1,2 Josefin Eklöf,1 Alexander Jordan,1 Tor Biering-Sørensen,3,4 Søren Sperling,5 Jens-Ulrik Stæhr Jensen1,2 1Department of Medicine, Section of Respiratory Medicine, Herlev and Gentofte Hospital, University of Copenhagen, Hellerup, 2900, Denmark; 2Department of Clinical Medicine, Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, 2200, Denmark; 3Department of Biomedical Sciences, Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, Denmark; 4Department of Cardiology, Copenhagen University Hospital Herlev and Gentofte Hospital, Hellerup, Denmark; 5Department of Respiratory Diseases and Allergy, Aarhus University Hospital, Denmark; Department of Clinical Medicine, Aarhus, 8000, DenmarkCorrespondence: Frida Vilstrup, Gentofte Hospitalsvej 1D, Hellerup, 2900, Denmark, Tel +45 41180072, Email Frida.vilstrup@regionh.dkObjective: Patients with chronic obstructive pulmonary disease (COPD) are a heavily comorbid group. Quinine is often used in the treatment of restless leg syndrome (RLS), although the adverse effects of the drug may be harmful for specific patient groups. The aim of this study was to determine the association between treatment with Quinine and the risk of acute exacerbations and mortality in patients with COPD, which has not previously been investigated.Methods: Analyses were performed on data from Danish national registries containing information about the relevant patients and their health, prescriptions, hospital admissions, and outpatient clinic visits. A propensity score matched cohort was created by matching the population on known predictors of the outcome, and an unadjusted Cox proportional hazards regression analysis was performed. Lastly, a multivariable Cox analysis was performed on the entire, unmatched population, adjusting for the same variables as used in the propensity matching.Results: The study population consisted of a cohort of 56,691 eligible patients with COPD, of whom 3,139 were exposed to Quinine. The propensity score matching led to two groups of 2,537 COPD patients, where one group was exposed to Quinine (cases) and the other group was not (controls). Exposure to Quinine was associated with an increased risk of exacerbations or death in a sensitivity analysis of the propensity-score-matched population (Hazard Ratio (HR) 1.130, 95% Confidence Interval (CI) 1.03 to 1.24). An unadjusted analysis on the unmatched population showed similar results (HR 1.475, 95% CI 1.39 to 1.56).Conclusion: In the current study, we found an association between the use of Quinine in patients with COPD and an increased risk of acute exacerbations and death. The results must be interpreted with attention to the observational nature of the study, and in order to definitively determine the association, further investigations should be performed.Keywords: COPD, pulmonary medicine, pharmacological interventions, COPD exacerbations